Long-term Stack splint immobilization for closed tendinous Mallet Finger - Hong, In Tae; Baek, Eugene; Ha, Cheungsoo; Han, Soo-Hong (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
Background Closed tendinous mallet finger can be treated non-operatively by extension splinting of the distal interphalangeal joint (DIPJ) for 6 to 8 weeks. However, method of conservative treatment in detail differs among various reports, especially in type of orthosis, duration of full-time immobilization and additional night orthotic wear after full-time immobilization. In our institution, full-time Stack splint is applied with distal interphalangeal joint (DIPJ) in extension for 12 weeks and night orthosis is worn for 4 weeks.Purpose The purpose of this study was to evaluate clinical and functional outcomes of tendinous mallet finger using our treatment protocol.Patients and Methods Between March 2007 and December 2017, patients with tendinous mallet finger who were managed conservatively according to our treatment protocol were retrospectively reviewed. A total of 100 patients (101 cases) were enrolled, including 77 males and 23 females. Extension lag was measured before, soon after treatment, and at the final follow-up. Flexion angle of DIP joint was measured at the final follow-up. Patients were clinically evaluated based on the Crawford classification scale and Abouna & Brown criteria.Results The mean age of patients was 40 years and the mean follow-up was 48 months. The mean extension lag was 28.3 degrees initially and 2.6 degrees at the final follow-up. (p-value < 0.001) Flexion angle at the final follow-up was 68.3 degrees. Based on the Crawford classification scale, 56 % of patients had excellent results, and 25 % of patients had good results. According to Abouna & Brown criteria, 78 % of patients had success results and 7.5 % of patients had improved results.Conclusions Wearing orthosis for up to 16 weeks (12 weeks full time and 4 weeks night orthosis) in the treatment of tendinous mallet finger injuries can achieve satisfying result.
Keywords: Tendinous Mallet finger; Stack splint